Mathematical methods for molecular science : theory and applications, visualizations and narrative - Straub, John Edward (New York : University Science Books, 2022)
"Mastery of key ideas in quantum mechanics requires knowledge of operators, differential equations, multidimensional integration, vector algebra, and functions of complex numbers. Statistical thermodynamics and kinetics require facility with partial differentiation, extremizing functions subject to constraints, and knowledge of differential equations. However, a treatment of these topics through specialized courses offered by mathematics departments is prohibitively time consuming for many molecular science majors in the fields of chemistry, biochemistry, biophysics, and materials science. Mathematical Methods for Molecular Science is designed to support a one-semester course that builds on the introductory calculus sequence and covers critical topics in multivariate calculus, ordinary and partial differential equations, and linear algebra"--
Includes bibliographical references (pages 529-530) and index.
Keywords: Molecular biology -- Mathematics; Biomathematics; Calculus